La responsabilidad social de la comunicación corporativa: Acción dinámica en la transformación social (2003)
The Corporative communication convokes towards a new way of exercising communication in and from the organizations, with ethics, responsibly and ample in its social effects in a way that contributes to the managerial development, without forgetting about the citizens who act within and around it. All communicative actions promoted by managerial interests that conceal individual interests must represent collective purposes and respond, then, to the managerial ethics of generating a conscience over the values that contribute to a more humane survival.